Challenges faced by secondary school teachers in integrating ICT into the curriculum: a multiple case study in the Grahamstown Circuit - Maholwana-Sotashe, Nikiwe Laura (Rhodes University, Faculty of Education, Department of Education, 2008)
The integration of Information and Communication Technology (ICT) into the curriculum has become the major issue worldwide. The education system does not only pursue the integration of ICT into the curriculum because of its popularity in the market system, but because of the role it is perceived to play in the changing curriculum (encourages active construction of knowledge). According to White Paper 7 e-Education policy (2004:17) every South African learner should be able to use ICTs confidently and creatively to develop the skills and knowledge they need to achieve personal goals and to be full participants in the global community by 2013. The central role played by teachers in teaching and learning requires them to have a holistic understanding of ICT integration. Furthermore they should be able to analyse when ICT integration is appropriate according to what is expected from the learner in the teaching and learning process. Drawing on the evidence from a survey of nine secondary schools in the Grahamstown Circuit of the Eastern Cape, this study examines how teachers from three different types of secondary schools: Former Department of Education (FDET) schools, Former House of Representatives (FHOR) schools and Former Model C (FMC) schools perceive the integration of ICTs in the curriculum. The salient ideas of how teachers perceive the integration of ICTs into the curriculum emerge from what they view as benefits of using ICT and what they view as challenges of integrating ICT into the curriculum. Contrary to expectations, the degree of ICT integration within the curriculum did not correspond directly with the availability of sufficient hardware, software or Internet connectivity at the participating schools.
Keywords: Educational technology -- South Africa -- Grahamstown; Education, Secondary -- South Africa -- Grahamstown -- Data processing; Information technology -- Study and teaching (Secondary) -- South Africa -- Grahamstown; Internet in education -- South Africa -- Grahamstown; Information technology -- South Africa -- Grahamstown; Computer-assisted instruction -- South Africa -- Grahamstown; Education, Secondary -- Curricula -- South Africa -- Grahamstown; Educational innovations